Pressure-Induced Assembly of Organic Phase-Change Materials Hybridized with Expanded Graphite and Carbon Nanotubes for Direct Solar Thermal Harvesting and Thermoelectric Conversion - Jie Ji; Yizhe Liu; Xiaoxiang Li; Yangzhe Xu; Ting Hu; Zhengzheng Li; Peng Tao; Tao Deng (Nanomaterials)
Direct harvesting of abundant solar thermal energy within organic phase-change materials (PCMs) has emerged as a promising way to overcome the intermittency of renewable solar energy and pursue high-efficiency heating-related applications. Organic PCMs, however, generally suffer from several common shortcomings including melting-induced leakage, poor solar absorption, and low thermal conductivity. Compounding organic PCMs with single-component carbon materials faces the difficulty in achieving optimized comprehensive performance enhancement. Herein, this work reports the employment of hybrid expanded graphite (EG) and carbon nanotubes (CNTs) to simultaneously realize leakage-proofness, high solar absorptance, high thermal conductivity, and large latent heat storage capacity. The PCM composites were prepared by directly mixing commercial high-temperature paraffin (HPA) powders, EG, and CNTs, followed by subsequent mechanical compression molding. The HPA-EG composites loaded with 20 wt% of EG could effectively suppress melting-induced leakage. After further compounding with 1 wt% of CNTs, the form-stable HPA-EG20-CNT1 composites achieved an axial and in-plane thermal conductivity of 4.15 W/m K and 18.22 W/m K, and a melting enthalpy of 165.4 J/g, respectively. Through increasing the loading of CNTs to 10 wt% in the top thin layer, we further prepared double-layer HPA-EG-CNT composites, which have a high surface solar absorptance of 92.9% for the direct conversion of concentrated solar illumination into storable latent heat. The charged composites could be combined with a thermoelectric generator to release the stored latent heat and generate electricity, which could power up small electric devices such as light-emitting diodes. This work demonstrates the potential for employing hybrid fillers to optimize the thermophysical properties and solar thermal harvesting performances of organic PCMs.